Low‐factor consumption for major surgery in haemophilia B with long‐acting recombinant glycoPEGylated factor IX. Issue 1 (1st August 2016) - Escobar, M. A.; Tehranchi, R.; Karim, F. A.; Caliskan, U.; Chowdary, P.; Colberg, T.; Giangrande, P.; Giermasz, A.; Mancuso, M. E.; Serban, M.; Tsay, W.; Mahlangu, J. N.
Abstract : Introduction: Surgery in patients with haemophilia B carries a high risk of excessive bleeding and requires adequate haemostatic control until wound healing. Nonacog beta pegol, a long‐acting recombinant glycoPEGylated factor IX (FIX), was used in the perioperative management of patients undergoing major surgery. Aim: To evaluate the efficacy and safety of nonacog beta pegol in patients with haemophilia B who undergo major surgery. Methods: This was an open‐label, multicentre, non‐controlled surgery trial aimed at assessing peri‐ and postoperative efficacy and safety of nonacog beta pegol in 13 previously treated patients with haemophilia B. All patients received a preoperative nonacog beta pegol bolus injection of 80 IU kg −1 . Postoperatively, the patients received fixed nonacog beta pegol doses of 40 IU kg −1, repeated at the investigator's discretion. Safety assessments included monitoring of immunogenicity and adverse events. Results: Intraoperative haemostatic effect was rated 'excellent' or 'good' in all 13 cases. Apart from the preoperative injection, none of the patients needed additional doses of nonacog beta pegol on the day of surgery. The median number of postoperative doses of nonacog beta pegol was 2.0 from days 1 to 6 and 1.5 from days 7 to 13. No unexpected intra‐ or postoperative complications were observed including deaths or thromboembolic events. No patients developed inhibitors. Conclusions: These results indicated that nonacog beta pegol was safe and effective in the perioperative setting, allowing major surgical interventions in patients with haemophilia B with minimal peri‐ and postoperative concentrate consumption and infrequent injections as reported with standard FIX products.